Relationship Between Gallstone Disease and Cardiometabolic Risk Factors in Elderly People with Non-Alcoholic Fatty Liver Disease - Hung MC (Dove Medical Press, 2020)
Man-Chen Hung,1 Chuen-Fei Chen,1 Meng-Ting Tsou,2 Hsin-Hui Lin,2 Lee-Ching Hwang,1,2 Ching-Ping Hsu2 1Department of Medicine, Mackay Medical College, New Taipei City, Taiwan; 2Department of Family Medicine, Mackay Memorial Hospital, Taipei, TaiwanCorrespondence: Ching-Ping HsuDepartment of Family Medicine, Mackay Memorial Hospital, No. 92, Sec. 2, Zhongshan N. Road, Zhongshan District, Taipei City 104, TaiwanTel +886-2-25433535Fax +886-2-25213847Email drhsuinfo@gmail.comBackground: The prevalence of gallstone disease (GSD) increases with age, and the elderly have a much higher mortality risk and incidence of surgical comorbidities. The aim of this study was to explore the relationship between GSD and cardiometabolic risk factors in elderly people with non-alcoholic fatty liver disease (NAFLD).Methods: In this cross-sectional study, we analyzed the data of elderly people who underwent annual health check-ups at a Northern Taiwan health examination center. These data were collected from physical examination, blood tests, abdominal ultrasonography, and medical histories. We excluded those with hepatitis B or C infections, heavy alcohol consumption, or cholecystectomy.Results: The analysis included 3,037 participants with a mean age of 73.6± 6.0 years. Over 70% were overweight or obese, and the overall prevalence of GSD was 17.7%. In our univariate analysis, GSD was positively correlated with age, body mass index, metabolic syndrome, diabetes mellitus (DM), hypertension (HTN), and various metabolic factors (fasting plasma glucose [FPG], triglyceride, uric acid, and high-density lipoprotein cholesterol [HDL-C] levels). After adjustment for age, gender, and body mass index, metabolic syndrome showed a positive association with GSD (odds ratio [OR] 1.31 [95% confidence interval [CI], 1.05– 1.64]; P=0.020). Specific components of metabolic syndrome that increased the risk for GSD in NAFLD elderly include lower levels of HDL-C (OR 1.35 [95% CI, 1.10– 1.66]; P< 0.001) and elevated FPG (OR 1.36 [95% CI, 1.10– 1.69]; P< 0.001).Conclusion: Our study concluded that GSD is significantly associated with metabolic syndrome in elderly people with NAFLD. Reduced HDL-C and elevated FPG both heighten the risk of developing GSD. Therefore, to lower the risk of GSD in NAFLD patients, their FPG levels and HDL-C levels must be regularly followed-up, and these patients should be educated about the symptoms of GSD if they meet the criteria for metabolic syndrome.Keywords: gallstone disease, cardiometabolic risk factors, metabolic syndrome